Pseudobasophilia: A Helpful Screening Tool in Diagnosis of Dengue - Mavra Fatima; Ayesha Younas; Ayisha Imran; Asma Nasir; Nauman Aslam Malik; Omar Rasheed Chughtai; Akhtar Sohail Chughtai (Proceedings, 2022)
Introduction: Pakistan is dealing with an epidemic situation of dengue. Serological testing for its diagnosis is not available everywhere across the country. So, in the current scenario, basophilia flagged by automated hematology analyzer can be a helpful screening tool in early diagnosis and prognosis of dengue in a resource limited country like ours.